PENGARUH FDR, NPF, CAR, DAN BOPO TERHADAP ROA PADA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) - Nurul Ichsan Hasan; R. Rizny Anindya Reswanty (Sekolah Tinggi Ekonomi Islam (STEI) Ar-Risalah Ciamis, 2021)
This study analyzes the influence Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), Operational Costs and Operating Income Against Return On Assets (ROA) BPRS in Indonesia Period from 2010-September 2017. The data used in this study is. Sampling technique used in this research is purposive sampling. The method of analysis used in this study is Multiple Regression Analysis using the computer program Eviews Software version 9 and Microsoft Excel 2013. The results in this study show that Financing to Deposit Ratio (FDR), Non Performing Finance (NPF), Capital Adequacy Ratio (CAR), and BOPO simultaneously have a significant effect on Return On Asset (ROA). Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) partially do not have a significant effect on Return On Aset (ROA).